Hospital X's Effective Strategy in Improving Patient Safety in the Era of the COVID-19 Pandemic - Cicih Wahyu Adiningsih; Iman Permana (Universitas Aisyah Pringsewu, 2023)
Patient safety issues during the Covid-19 pandemic and the strategies implemented to improve it. This paper aims to find out strategies in improving patient safety in the era of the COVID-19 pandemic. This research is included in the type of descriptive qualitative research with case study methods or approaches (Case Studies) and observations. The results show that six patient safety goals have been implemented, but management support is needed to improve patient safety, especially in terms of optimizing service quality, regulatory policies, socialization, and staff training. Lack of officer awareness and commitment to incident reporting are obstacles to changing safety cultures. Strategy optimization is carried out by improving human resources and meeting patient perceptions of patient safety, such as services in accordance with procedures, handling speed, cleanliness of standardized rooms and infrastructure, and the availability of patient aids in hospitals. Optimization of the strategic plan is carried out by streamlining human resources (HR), patient perceptions of patient safety in hospitals including services that are in accordance with procedures, services based on handling speed, the presence of officers who are always on standby, responsive and competent attitudes, information about the flow of hospitals and clear patient referral systems, cleanliness of standardized rooms and infrastructure, completeness of waiting room facilities, and the availability of patient aids in hospitals.